2020
DOI: 10.1002/jhbp.839
|View full text |Cite|
|
Sign up to set email alerts
|

Accurate prediction of severe postoperative complications after pancreatic surgery: POSSUM vs E‐PASS

Abstract: Despite recent advances in the perioperative management of surgical patients and operative techniques, there is still a high incidence of postoperative complications (PCs) such as postoperative pancreatic fistula (POPF) after pancreatic surgery which can lead to life-threatening complications including intra-abdominal infections, severe sepsis, and massive bleeding. The most commonly used assessment tools for the prediction of PCs after gastrointestinal surgery are the physiological and operative severity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The PRS, SSS and CRS values are shown from top to bottom in order (Figure 3A ). In the PRS analysis, a total of 2183 patients participated in 10 studies[ 11 , 16 , 19 - 26 ] that reported the relationship between PRS scores and postoperative complications. The mean value of PRS in the group with complications was 0.45, and that without complications was 0.40.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PRS, SSS and CRS values are shown from top to bottom in order (Figure 3A ). In the PRS analysis, a total of 2183 patients participated in 10 studies[ 11 , 16 , 19 - 26 ] that reported the relationship between PRS scores and postoperative complications. The mean value of PRS in the group with complications was 0.45, and that without complications was 0.40.…”
Section: Resultsmentioning
confidence: 99%
“…Since the data had significant heterogeneity ( I 2 = 87%), sensitivity analyses were performed by using a fixed-effect model and removing two low-quality studies[ 16 , 21 ]. The results showed that the SSS score in the group with complications was 0.06% higher than that in the group without complications, which was reliable for the homogeneity of the two groups [MD (95%CI): 0.06 (0.04-0.09), P < 0.0001, I 2 = 0].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations